2009
DOI: 10.1039/b822247a
|View full text |Cite
|
Sign up to set email alerts
|

Low-coverage adsorption properties of the metal–organic framework MIL-47 studied by pulse chromatography and Monte Carlo simulations

Abstract: Low-coverage adsorption properties of the metal-organic framework MIL-47 were determined by a combined experimental and simulation study. Henry constants and low coverage adsorption enthalpies of C5-C8 linear and branched alkanes, cyclohexane and benzene were measured from 120 to 240 degrees C using pulse gas chromatography. An adapted force field for linear and branched alkanes in MIL-47 was used to compute the adsorption properties of those molecules. A new set of charges was developed for simulations with b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
87
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(92 citation statements)
references
References 65 publications
5
87
0
Order By: Relevance
“…14,41 Because the goal of this study is to probe the behaviour of water adsorption in a series of functionalised variants of the Al(OH)(1,4-ndc) MOF, and also because little experimental thermodynamic data is available on this particular system, we used a very simple approach to adjust the partial atomic charges of the host material. We used as a starting point the partial charges determined by Calero et al in a recent study of the related material MIL-47, 42 in which benzenedicarboxylate ligands connect one-dimensional V(OH) chains to form lozenge-shaped pores. We then scaled all the partial charges down to better reproduce the experimental adsorption isotherm.…”
Section: Determination Of Partial Charges For the Mofmentioning
confidence: 99%
“…14,41 Because the goal of this study is to probe the behaviour of water adsorption in a series of functionalised variants of the Al(OH)(1,4-ndc) MOF, and also because little experimental thermodynamic data is available on this particular system, we used a very simple approach to adjust the partial atomic charges of the host material. We used as a starting point the partial charges determined by Calero et al in a recent study of the related material MIL-47, 42 in which benzenedicarboxylate ligands connect one-dimensional V(OH) chains to form lozenge-shaped pores. We then scaled all the partial charges down to better reproduce the experimental adsorption isotherm.…”
Section: Determination Of Partial Charges For the Mofmentioning
confidence: 99%
“…The 3D framework type MIL-47(V) built up from infinite chains of corner sharing V 4+ O 6 octahedra interconnected by 1,4-benzenedicarboxylate groups, thus generating 1D-channels with a free diameter of 11 Â 10 Å [36], has been selected for its structural and chemical features (absence of both defects in the pore walls and structural changes upon inclusion of guest molecules) that allow a systematic measurement of D s for all the investigated n-alkanes. Beyond a fundamental interest, the knowledge gained from this study will be complementary to the equilibrium adsorption measurements published elsewhere to help the interpretation of the promising adsorption properties of this MOF-type material for alkanes [15,17,18] or other complex molecules such as xylenes [37,38].…”
Section: Introductionmentioning
confidence: 96%
“…Apart from the light hydrocarbons, it was also evidenced that such a class of hybrid MOFs shows interesting topological and chemical features that favor either large adsorption uptakes for longer chain hydrocarbons in the vapor and liquid phases or high selectivities for the separation of aromatics (xylenes) and aliphatics (hexane) isomers [14], both characteristics being also of upmost industrial interests in petrochemistry. These later conclusions were mainly deduced from equilibrium adsorption studies conducted both experimentally and computationally [15][16][17][18], while only a few investigations have focused on the dynamics of the hydrocarbons within the porosity of these MOFs that is expected to significantly impact the adsorption/separation processes. Indeed, the exploration of the dynamics has been mainly concentrated on the diffusion of short and intermediate length linear alkanes in a wide series of MOFs.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years a great number of studies have demonstrated the unique potential of Metal-Organic Framework (MOF) [8][9][10][11][12][13][14] [15] and Zeolite Imidazolate Framework (ZIF) [16][17][18][19] materials for the adsorption and separation of CO, CO 2 , CH 4 and H 2 gases, due to their extremely high porosity [20], characterised by large surface areas and pore diameters [21]. In conjunction with experimental techniques, the use of simulation in modelling the adsorption properties of MOFs [8,[22][23][24][25][26] and ZIFs [27][28][29] has been increasingly established as a powerful tool in the design of new materials with enhanced affinity and selectivity for CO 2 .…”
Section: Introductionmentioning
confidence: 99%